2020
DOI: 10.1177/2514848620945321
|View full text |Cite
|
Sign up to set email alerts
|

Making insects tick: Responsibility, attentiveness and care in edible insect farming

Abstract: Insects are increasingly promoted as a sustainable and nutritious source of protein, with ‘edible insect’ sectors emerging in many countries not traditionally associated with their consumption. A number of studies have examined the attitudes of potential consumers to eating insects but the understandings and practices of farmers have largely been ignored. This article expands nature-society scholarship’s engagement with the edible insect sector by investigating how farmers make sense of their responsibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…In addition, few guidelines specifically mention animal welfare as an aspect to consider when keeping insects. Consequently, insect farmers often have to guess and 'trial-and-error' best practices [22,25,26]. Interviewing twelve insect farmers and one representative of the insect industry in the UK, Bear [25,26] exemplifies how producers perceive and cope with the "ethical ambiguity of insect production" [26] (p. 1011).…”
Section: Aspects Concerning the Animal Welfare Of Insectsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, few guidelines specifically mention animal welfare as an aspect to consider when keeping insects. Consequently, insect farmers often have to guess and 'trial-and-error' best practices [22,25,26]. Interviewing twelve insect farmers and one representative of the insect industry in the UK, Bear [25,26] exemplifies how producers perceive and cope with the "ethical ambiguity of insect production" [26] (p. 1011).…”
Section: Aspects Concerning the Animal Welfare Of Insectsmentioning
confidence: 99%
“…Consequently, insect farmers often have to guess and 'trial-and-error' best practices [22,25,26]. Interviewing twelve insect farmers and one representative of the insect industry in the UK, Bear [25,26] exemplifies how producers perceive and cope with the "ethical ambiguity of insect production" [26] (p. 1011). Regarding acceptable slaughter methods, for example, one insect farmer reported that they had to "make it up" [25] (p. 760), and another farmer stated: "I wouldn't have thought being frozen stiff was especially nice, but I have no idea and it just seems to be a reasonable way to do it" [25] (p. 761).…”
Section: Aspects Concerning the Animal Welfare Of Insectsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Appel & Elwood, 2009;Crook, 2021). This is important morally, as insects are subjected to potentially-painful stimuli in research and farming (Bear, 2021). It is also an important consideration for modelling human pain disorders.…”
Section: The Significance Of Insect Descending Nociception Controlsmentioning
confidence: 99%
“…Recent suggestions to think with care in science and technology studies (Puig de la Bellacasa, 2011) and "to take a more critical stance toward the politics of care in technoscience" (Murphy, 2015, p. 719) manifest further mutual interaction between the concepts of care and maintenance. Whereas the concept of care is increasingly applied to non-human agents (Bear, 2020;Beckett, 2020;Denis & Pontille, 2015;Martin et al, 2015;Puig de la Bellacasa, 2015;Schrader, 2015;Ureta, 2014Ureta, & 2016Viseu, 2015), maintenance and repair studies still focus primarily on technologies and infrastructures. This article aims to extend the realm of maintenance and repair to explore humans' bodily and material caretaking activities.…”
Section: Bridging Care and Maintenance Through Emotional Engagementsmentioning
confidence: 99%